Terras de preto no Vale do Rio Munim: Nina Rodrigues, historicidades e territorialidades (1988-2008) - Sousa, José Reinaldo Miranda de (2009)
The objective of this is to analyze terras de preto within the state of Maranhão, more precisely within the municipal district of Nina Rodrigues region of Munim river s valley, and its focus being the settlement Balaiada and the village Amapá dos Catarinos and, with that, bring to history s stage questions until now hidden, related to these village s inhabitants, their strive for land and better conditions of survival and work. Also dealt with questions related to the land possessions within the state, to comprehend the context in which the municipal district object of the research is inserted. The literature research and other documents related to this segment of population, also as the testimonials of people of those villages, were meaningful to comprehend their history and contemporaneous strives for the ownership of lands where they inhabit. In this study we can notice the importance of identities construction as a fundamental element for the constitution of the territory